Students' progression to postgraduate studies : an exploratory study on demographic attributes among Psychology Honours students at the University of Cape Town - Fowler, Gillian Catherine (Department of Psychology, 2015)
South Africa does not produce enough Doctoral graduates each year compared to other developed and developing countries. There are also too few Black and female graduates. Black postgraduates are particularly underrepresented in psychology in South Africa. This is problematic for future knowledge producers. Gender, race, age, marital status, institutional and socioeconomic issues, and academic performance play a role in progression to postgraduate studies. The current study aimed to explore: (a) the demographic and academic characteristics of a cohort of Psychology Honours students at the University of Cape Town; (b) whether there was an association between gender and enrolling or not enrolling in postgraduate studies; (c) whether there was an association between race and enrolling or not enrolling in postgraduate studies; (d) whether there was an association between academic performance and enrolling or not enrolling in postgraduate studies; (e) what students' reasons were for deciding to enroll or not to enroll in postgraduate degrees after Honours.